Research on Solutions for Algebraic and Transcendental Diophantine Equations - Pooja Devi, Anjana Rajoria (Mathematical Statistician and Engineering Applications, 2022)
When it comes to number theory, Diophantine approximation is the field of number theory that deals with questions such as whether or not an integer is rational, irrational, or transcendental. On the other hand, one can ask how well an irrational number approximates a rational number, or how well algebraic numbers approximate a transcendental number. Two expressions are placed at the same value, One way to describe an algebraic equation is a mathematical statement. Variables, coefficients, and constants are the main components of an algebraic equation in most cases.